The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5ra00678c
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of heptadecane in hydrocarbon polluted dune sands using a newly-isolated thermophilic bacterium, Brevibacillus borstelensis TMU30: statistical evaluation and process optimization

Abstract: An enrichment culture was established to isolate a thermophilic hydrocarbon-degrading bacterium from contaminated soil samples from the Tehran Petroleum Refinery. The bacterium was characterized based on 16S rRNA and identified as Brevibacillus borstelensis TMU30. It is registered at NCBI under accession number KF181624.1. The capability of the bacterium for degradation of heptadecane as a representative contaminant in polluted dune sand was evaluated in a slurry bubble column bioreactor. The aeration rate, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At 48 d, the oil concentration in tank A had reduced to 2.28 mg L À1 , which means that strain S-1 catabolized the crude oil as a carbon and energy source so it reduced the DPH content. 35,36 The degradation removal percentage of the DPHs was about 33.72%, including physical and chemical degradation such as weathering and catabolizing.…”
Section: The Oil Content Changes In Seawatermentioning
confidence: 99%
See 1 more Smart Citation
“…At 48 d, the oil concentration in tank A had reduced to 2.28 mg L À1 , which means that strain S-1 catabolized the crude oil as a carbon and energy source so it reduced the DPH content. 35,36 The degradation removal percentage of the DPHs was about 33.72%, including physical and chemical degradation such as weathering and catabolizing.…”
Section: The Oil Content Changes In Seawatermentioning
confidence: 99%
“…In this study because the emulsication of GM-2 caused the DPHs to increase, the crude oil in the sediment peaked at 21 d, which is consistent with the dispersant enhancing the sorption extent. 35 Dispersants make crude oil content decrease, but at the same time, they may increase oil pollution in tidal ats. Fig.…”
Section: The Oil Content Changes In Sedimentmentioning
confidence: 99%
“…4,14,17,18 Genera collected from these sites have been limited to Bacillus, Geobacillus, Thermoactinomyces, and Brevibacillus. 19,20 Only four studies on hydrocarbon degradation by Anoxybacillus have been reported, [21][22][23][24] where the degraded compounds were aromatic. As a new thermophilic genus, Anoxybacillus could be utilized in a large number of applications as previously described, 25 however these applications are currently limited to the hydrolysis of starch and lignocellulosic biomasses, not the degradation of alkanes.…”
Section: Introductionmentioning
confidence: 99%